Analysis of the response mechanisms of Pinellia ternata to terahertz wave stresses using transcriptome and metabolic data - Wang, Dongdong; Sarsaiya, Surendra; Qian, Xu; Jin, Leilei; Shu, Fuxing; Zhang, Chuanyou; Chen, Jishuang (Frontiers in Plant Science, 2023)
Pinellia ternata (Thunb) Breit (Araceae), a significant medicinal plant, has been used to treat various diseases for centuries. Terahertz radiation (THZ) is located between microwaves and infrared rays on the electromagnetic spectrum. THZ possesses low single photon energy and a spectral fingerprint, but its effects on plant growth have not yet been investigated. The study's primary objective was to examine the transcriptome and metabolome databases of the SY line to provide a new perspective for identifying genes associated with resistance and growth promotion and comprehending the underlying molecular mechanism. Variations in the biological characteristics of P. ternata grown under control and experimental conditions were analyzed to determine the effect of THZ. Compared to the control group, phenotypic variables such as leaf length, petiole length, number of leaves, leaf petiole diameter, and proliferation coefficient exhibited significant differences. P. ternata response to THZ was analyzed regarding the effects of various Coercions on root exudation. The experimental group contained considerably more sugar alcohol than the control group. The transcriptome analysis revealed 1695 differentially expressed genes (DEGs), including 509 upregulated and 1186 downregulated genes. In the KEGG-enriched plant hormone signalling pathway, there were nineteen differentially expressed genes, thirteen of which were down-regulated and six of which were up-regulated. In the metabolomic analysis, approximately 416 metabolites were uncovered. 112 DEMs were down-regulated, while 148 were up-regulated. The P. ternata leaves displayed significant differences in phytohormone metabolites, specifically in brassinolide (BR) and abscisic acid (ABA). The rise in BR triggers alterations in internal plant hormones, resulting in faster growth and development of P. ternata. Our findings demonstrated a link between THZ and several metabolic pathway processes, which will enhance our understanding of P. ternata mechanisms.